RAÍZES PARINTINTIN: RECONNECTING WITH INDIGENOUS HISTORY AND SOCIALIZATION IN THE AMAZON - Pereira, Leidiane Gomes; de Paula, Adrielly Carvalho; Leal, Gizele Carvalho (Seven Editora, 2025)
This study is a sociocultural research, through a qualitative approach, which aims to understand and analyze the identity of the cultural manifestations of the indigenous community "Pupunha", of the Parintintin ethnic group, located in the municipality of Humaitá – AM, as a process of formation and cultural and socio-environmental transformation. As well as, consider the importance of knowing the Amazonian culture beyond the theoretical context. This text addresses a field study – technical visit, carried out in 2023, at the São José Indigenous Municipal School, incorporated into the Pupunha community. The purpose of the research was to facilitate the understanding of the modernization process in the socializing matrix of the Amazonian identity; promote intercultural dialogue between local society (Humaitá) and the Parintintins, and encourage the exchange of knowledge and experiences between indigenous and non-indigenous students. In addition, we directed non-indigenous students from the Governador Plínio Ramos Coelho State School – GM3, from the 1st grade classes to learn about the cultural identity of their region.DOI: https://doi.org/10.56238/sevened2025.021-014